Teachers’ Sense of Meaning Associations With Teacher Performance and Graduates’ Resilience: A Study of Schools Serving Students of Low Socio-Economic Status - Lavy, Shiri; Ayuob, Wesam (Frontiers in Psychology, 2019)
Adolescents from lower socio-economic status (SES) often experience distress in their personal life as well as at school. Moreover, their ability to overcome such difficulties and pave their path to a higher SES depends, to a certain extent, on their ability to develop resilience despite their disadvantaged background. Acknowledging the critical contribution of teachers to students' development, in the present study we focused on teachers as agents who may influence graduates' resilience, and on their sense of meaning at work - a resource these teachers may draw upon to increase their performance and contribute to their disadvantaged students and to their relationships with them. Specifically, we postulated that teachers’ sense of meaning at work will be associated with teachers’ performance, and that teachers’ relationships with their students would mediate this association, as they serve as the main vehicle through which teachers impact their students. We further suggested that teachers’ sense of meaning would have long-term effects on students’ coping abilities, reflected in school graduates’ resilience levels. The study comprised 857 participants, teachers and graduates, from 30 Arab vocational schools in Israel, comprising mainly low SES students. Teachers (N = 436) completed self-report measures of their sense of meaning at work, relationships with students, and performance. Furthermore, to reveal potential long-term effects of teachers’ sense of meaning at work, school graduates (N = 421) completed measures of their relationships with teachers and resilience. Analyses indicated a significant association of teachers’ sense of meaning with their performance, which was mediated by teachers’ reports of their relationships with students. Furthermore, teachers' sense of meaning at work and graduates' perceptions of their relationships with the teachers were both significantly associated with graduates' resilience. The findings highlight teachers’ sense of meaning at work as a potential contributor to their performance, which may also contribute to students’ resilience in lower SES schools. They point to teachers’ sense of meaning as a potential resource for teachers of lower SES students, and highlight the importance of nurturing and developing it in various programs and practices (e.g., teacher training, teacher development, organizational routines).